“I Cannot See the Day They Will Make a New Chief”: Historically Created Uncertainties about Sacred, Kingly, Populist and Secular Values in Lau, Fiji - Pauwels, Simonne (Anthropologica, 2020)
In Fiji, Lauan paramount chiefs have always been sacred – kingly and populist – but through time they also became secular chiefs – representatives of the colonial power and later politicians and statesmen. For some, the status of sacred chief had to consolidate their secular status, for others, their status of secular chief received the illusion of sacredness through title manipulation. The latter were even subject to territorial expansion. Chiefs themselves, whether secular, sacred or both, maintained a confusion between sacred and secular rights and duties. Recent fieldwork reveals grumbling and frustration among the Lauans, as these facts created a multitude of points of view they increasingly expressed because of the absence of a paramount chief for 13 years. This made them less respectful toward the title and resulted in the feeling of being able to do without a paramount chief. At the same time, however, the contradictory idea that a chief is the only person who can restore the value of respect and order into the community is still vivid.